Non-native Forest Insects and Pathogens in Australia: Establishment, Spread, and Impact - Nahrung, Helen F.; Carnegie, Angus J. (Frontiers in Forests and Global Change, 2020)
Geographic isolation, unique native flora and a robust biosecurity system have resulted in Australia remaining free from many of the devastating exotic pests and pathogens found in other countries. Nevertheless, at least 260 non-native arthropods and pathogens of forest hosts have established in Australia since 1885. Although the risk of invasive species arriving and establishing in Australia is increasing through raised levels of trade and travel, the rate of establishment of non-native forest pests has remained relatively constant over the last 130 years, accumulating at a rate of about two per year. The majority of these are arthropods and pathogens of tree host genera exotic to Australia, including the main plantation species, Pinus radiata; few are significant pests of tree host genera native to Australia. Eighteen percent of these pests have caused moderate to significant impact or resulted in ongoing management costs in commercial plantations, native forests or amenity trees. Asian and European species accounted for two-thirds of Australia’s non-native forest pests, and were equivalently represented numerically, temporally and compositionally. Asian species were more polyphagous and more frequently established in northern Australia, possibly reflecting climatic similarity, geographic proximity, and host plant suitability. Earlier-establishing species were more polyphagous and had broader Australian and global non-native distributions. We here provide the first comprehensive database of non-native arthropod and pathogen species of relevance to Australia’s plantation, amenity and native forest trees in Australia. This knowledge will assist with identifying key traits of exotic pest threats to forests in Australia and globally to inform national and international biosecurity policy.